Republic of Madagascar : Tourism Sector Study - Christie, Iain T.; Crompton, D. Elizabeth (World Bank, Washington, DC, 2013)
Madagascar has an impressive array of biodiversity, natural beauty and cultural resources to support tourism. Surprisingly, of the 200,000 visitors the island per year, only about 60,000 come expressly for tourism, the rest traveling for other reasons but which could include some tourism activity. Madagascar has the potential to welcome many more tourists if the sector's growth is well planned in a broad, multi-sectoral way - focusing on economic aspects, infrastructure and environmental and social concerns, particularly for community participation. This report sets outs a program for equitable development of the sector and evaluates the opportunities for growth and the barriers that currently block progress. The report features a survey of hotels and other tourism establishments. The report recommends a comprehensive master planning program and action program.